Study on the Effect of \(β\)-Cyclodextrin on Phospholipids and Cholesterol of the Milk Fat Globule Membrane - Alonso , Leocadio; Cuesta, Paloma; Calvo, María V.; Fontecha, Javier (Emerging Challenges in Agriculture and Food Science Vol. 4, 2022)
Phospholipids are located on the milk globule membrane (MFGM) with the cholesterol. The purpose of this research was to investigate the effect of \(β\)-cyclodextrin (\(β\)-CD) on phospholipids and cholesterol in raw pasteurized milk with the goal of removing cholesterol from the milk fat. Total phospholipids decreased slightly in \(β\)-CD treated milk, but the impact of the \(β\)-CD was not significant. \(β\)-CD is an effective oligosaccharide for removing cholesterol from milk, with a reduction of more than 97 percent, and has no impact on individual phospholipids of the milk fat globule membrane (phosphatidylcholine, phosphatidylethanolamine, sphingomyelin, phosphatidylinositol, and phosphatidylserina).